Fostering Trustworthy (Amanah) Character: Investigating the Impact of Integrating Religious Values into Thermochemical Module - Mawaddah, Mawaddah; Sulastri, Sulastri; Evendi, Evendi (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2023)
The character of trustworthy (amanah) is fundamental to the inherent constitution of the human psyche, and its integration is crucial in daily practices. Thermochemistry, as a chemical discipline intricately connected to the ambient environment, encapsulates latent character values that often remain unarticulated within the educational discourse. This research aims to determine the effectiveness of a thermochemical module containing religious values on forming a trustworthy (amanah) character in the chemistry learning process. This research uses a quasi-experimental type with a one-group pretest and posttest design to examine the effectiveness of the module that has been developed. Data collection is taken from a pretest and posttest character assessment sheet comprising five indicators. Besides, the data analysis technique was descriptively based on the N-gain test. The results showed an increase in the formation of students' trustworthy (amanah) character after using the thermochemical module containing religious values, where the average pretest percentage was 68.42% in the sufficient category (starting to appear) to the average posttest percentage of 78.92% in the good category (starting to develop). In addition, the average N-gain score was 0.56 in the medium category, and the average N-gain score percentage was 56.16%, with the interpretation being quite effective. Hence, this data shows that the thermochemistry module containing religious values was helpful in the chemistry learning process and influenced the formation of trustworthy (amanah) character.